Water dynamics in the soil-plant-atmosphere continuum in semiarid forests - Costa, Juliana Alcântara (2022)
The movement and storage of water in forests play an important role in the integrated planning, development and management of water resources. These processes are particularly relevant in semi-arid regions. This document is divided into three chapters organized in the format of scientific articles. The entire PhD dissertation is based on the study of ecohydrological phenomena that occur in the soil-plant-atmosphere continuum. The chapters follow a broad line of investigation, starting with a more detailed hydrological process in a smaller area and ending with an approach in larger areas. The first chapter (I) is the one that, of the three, goes deeper into the study of the processes that occur in the soil-plant-atmosphere continuum, dealing with the variation of water storage in the plant in Caesalpinia pyramidalis Tul. and its relation to external events. In this first study, the Caatinga was used as an area designation. It was observed that the emergence of leaves occurred with a stem moisture of 0.32 m3.m-3. Catingueira plants are able to absorb water below the potential commonly determined as permanent wilting point (-1.5 MPa). The volume of water stored in the plants represents 17% of the maximum volume observed in the reservoir that receives all the water drained from the hydrographic basin during the study period. In the second chapter (II) it was intended to deepen the study of one of the phenomena related to evapotranspiration, the sap flow in the plant. In addition, in the second chapter, the study area was expanded to Tropical Seasonally Dry Forest, studying in particular the species Caesalpinia pyramidalis Tul., popularly known as catingueira, which is a strong representative of the biome that gives it its name. It was identified that catingueira plants have the ability to perform inverse sap flow at night and predawn basically throughout the year. Higher sap flow was observed in the transition seasons due to atmospheric conditions and soil moisture. There was a superiority of 46% of the catingueira sap flow in the rainy season compared to the dry season. It was noticed that the nocturnal sap flow is more significant in the driest months, demonstrating another adaptive strategy of the species. The third and final chapter (III) is the one with the broadest spatial approach of the three. The study deals with the hydrological process of evapotranspiration, which was carried out for two distinct semi-arid zones, one in Brazil (Caatinga) and another in Spain (Pinares), using remote sensing. It was found that the annual amplitude of potential evapotranspiration (ET0) is the same in both areas, but the values of the Caatinga are higher. The Caatinga forest presented greater spatial variation of real Evapotranspiration (ETa) than the Pinares forest, as well as a greater extension with less temporal stability of the ETa than the Pinares forest. Both the Caatinga forest and the Pinares forest showed significant positive trends in annual ET0 and ETa. We estimate that the value of ETa increases faster in Pinares than in the Brazilian Caatinga. Taking the Caatinga as a hydrological mirror, some consequences are expected for Pinares, such as significant changes in the water balance, increased vulnerability of biodiversity and reduced water availability in the soil and in reservoirs.